2007
DOI: 10.1002/ijc.22989
|View full text |Cite
|
Sign up to set email alerts
|

Variants of chemokine receptor 2 and interleukin 4 receptor, but not interleukin 10 or Fas ligand, increase risk of cervical cancer

Abstract: Cervical cancer is caused by persistent infection of oncogenic human papillomavirus (HPV). Most infected women clear the virus without developing cervical lesions and it is likely that immunological host factors affect susceptibility to cervical cancer. The impact of the human leukocyte antigen (HLA) locus on the risk of cervical cancer is established and several other genes involved in immunological pathways have been suggested as biologically plausible candidates. The aim of this study was to examine the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
4
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 58 publications
2
54
4
4
Order By: Relevance
“…Based on a literature search and selection, a total of 10 publications (11)(12)(13)(14)(15)(16)(17)(18)(19)22) comparing the FAS/ FASL polymorphism and cervical cancer susceptibility were identified. Among these studies, 1 study was in Chinese (22) and 1 study contained data on two different ethnicities (18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a literature search and selection, a total of 10 publications (11)(12)(13)(14)(15)(16)(17)(18)(19)22) comparing the FAS/ FASL polymorphism and cervical cancer susceptibility were identified. Among these studies, 1 study was in Chinese (22) and 1 study contained data on two different ethnicities (18).…”
Section: Resultsmentioning
confidence: 99%
“…Although evidence of an association between FAS/FASL polymorphisms and cervical cancer risk has been reported, the findings remain controversial (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Therefore, we performed a meta-analysis of all published studies on the association between the FAS/FASL polymorphisms and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The genotype predisposing to the production of high levels of IL-10 is more commonly observed in cervical cancer patients, compared to healthy women (17). However, findings of a previous suggested that the variants of chemokine receptor 2 and IL-4 receptor, rather than IL-10 or Fas ligand, increase the risk of cervical cancer (18).…”
Section: Introductionmentioning
confidence: 95%
“…This points to the importance of the immune response toward HPV infection in preventing carcinoma development and explains why genetic variations in genes of immunological pathways, in addition to the HLA class II genes, [6][7][8][9][10][11][12] are associated with in situ (2011) 12, 605 -614. and invasive cervical cancer. 9,[14][15][16][17][18] However, only a handful of the identified genes show a consistent effect in multiple cohorts, and thus additional risk factors for persistent infection and tumor development are likely to exist. Assuming that variation in genes with a specific function is of particular interest, there are several optional study designs.…”
Section: Introductionmentioning
confidence: 99%